Four More Years: Presidential Elections, Comparative Mindset, and Managerial Decisions - Xu, Alison Jing; Moorman, Christine; Qin, Vivian Yue; Rao, Akshay R. (Academy of Management Journal, 2020)
Presidential elections reflect societal-level events that expose citizens to large amounts of comparative political information. We suggest that this exposure activates a “comparative mindset” that changes managers’ business decisions in nonpolitical domains. In this state, managers are more likely to select from available options and increase their spending level. Four studies demonstrate this effect. Study 1 uses a quasi-experiment to show that U.S. firms, but not non-U.S. firms, spend more on advertising in U.S. presidential election years versus nonelection years. In a controlled business simulation, Study 2 shows that participants spend more on advertising and training in presidential election years versus nonelection years. Two experiments involving practicing managers follow. Study 3 exposes managers to comparative political information featuring a U.S. Senate election; we observe an increase in spending on training and development programs. Study 4 exposes managers to comparative political information for state-level political races, finding that doing so reduces the importance of negative information in the subsequent managerial decision process and leads to increased marketing spending. Moreover, shifting the decision frame from selecting to rejecting options restores the focus on negative information and attenuates the effect. We conclude with a discussion of the research’s theoretical and practical contributions.